FATORES QUE AFETAM A GESTÃO DE CONTRATOS PSICOLÓGICOS NA UNIVERSIDADE FEDERAL DE SANTA CATARINA-UFSC - Alessandra de Linhares Jacobsen (Universidade Federal de Santa Catarina, 2016)
This article aims to analyze the influence of the psychological contra cts factors in the Philosophy and Human Sciences Centre (CFH/UFSC) in order to support the management in this kind of institution. The methodology was predominantly qualitative, descriptive and case study. Data collection techniques used were the bibliogra phical research, documentary research and the questionnaire administered to selected subjects, not probabilistic, considering accessibility and typicality. The questionnaire consisted of closed questions multiple - choice and Likert scale. Data were statisti cally analyzed by interpretative analysis. The results presented the most influential psychological contracts factors and some suggestions were given to correct deficiencies identified by the survey. It was concluded that the most influential factors are f avorable for psychological contracts in balance, but there are others to be improved. It is suggested to be aware of the importance of psychological contracts, clear and constant communication since the beginning and committee formation to manage such cont racts.